Pengembangan Modul Ajar IPAS Terintegrasi Numerasi untuk Meningkatkan Kemampuan Bernalar Kritis Siswa Fase C - Subekti, Ihwan; Nuraeni, Cici (Jurnal Didaktika Pendidikan Dasar, 2024)
This study aims to develop and evaluate the effectiveness of an integrated numeracy IPAS teaching module to enhance students'critical reasoning abilities. The research employed a Research and Development (R&D) approach with the Define, Design, and Development model, utilizing a One Group Pretest-Posttest Experimental Design scheme on 10 fifth-grade students of SDN 2 Cimanggu. Data collection methods included interviews, observations, teacher and student response questionnaires, and learning outcome tests. The developed teaching module achieved validity rates of 70.56% for media and 74.67% for content, categorized as "valid". The practicality of the module was highly rated based on teacher 81.00% and student 78.80% response questionnaires. Students' average critical reasoning ability was recorded at 52.5 in the pretest. After utilizing the integrated numeracy IPAS teaching module, there was a significant improvement, with average critical reasoning ability reaching 81.25. The N-Gain test results showed improvements in cognitive learning achievement 0.425 and critical reasoning ability reaching 0.6417, confirming that the integrated numeracy IPAS module has a significant positive impact. In conclusion, the integrated numeracy IPAS teaching module effectively enhances students' critical reasoning abilities, indicating potential for improving critical reasoning skills in the learning process.